Peran Kepercayaan dalam Memediasi Pengaruh Celebrity Endorser, Online Customer Review, dan Online Customer Rating Terhadap Minat Beli pada Produk Lipstik Wardah di E-Commerce Shopee - Regita Kurnia Prahesti; Vincent Didiek Wiet Aryanto; Aries Setiawan; Adilla Kustya Ulfa (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2026)
Wardah's market share fell from 27.2% (2022) to 15% (2025), even though Wardah Matte Lip Cream has 268,700 reviews with a rating of 4.9 on Shopee. This study aims to determine the role of celebrity endorsers, online customer reviews, and online customer ratings on the purchase interest of Wardah lipsticks on Shopee, with consumer trust as a mediating variable. The research method used a quantitative approach through the distribution of questionnaires to consumers who had purchased Wardah products on Shopee. Data analysis was performed using Smart PLS software. The results of this study can contribute to companies in designing more effective digital marketing strategies based on consumer trust. The results show that celebrity endorsers and online customer reviews have a significant positive effect on purchase intention, while online customer ratings do not directly affect purchase intention but have a significant effect on trust. Furthermore, trust was found to mediate the relationship between the three independent variables and purchase intention, indicating that trust is a key factor in the consumer purchase decision-making process.